Economic approaches to organizations - Douma, Sytse; Schreuder, Hein (Prentice Hall, 2008)
*"Why do Organizations exist?" " *""What is the relationship between markets and organizations?" " " *"When does one perform better than the other? " " " "The Answers: Economic Approaches to Organizations. " " " "Now in its fourth edition, Economic Approaches to Organizations" "remains one of the few texts to emphasize the importance of economic issues and developments in the study of organizations and management. " " It explains in a non-technical way economic approaches such as behavioural theory of the firm, game theory, agency theory, transaction cost economics, economics of strategy and evolutionary approaches. This latest edition also shows how different economic approaches are applied in practice with a new Part III Applications. New to the fourth edition: * New part III Applications includes 3 new chapters on mergers and acquisitions, hybrid forms (like joint ventures, business groups and franchising) and corporate governance. * Step by- step conceptual framework to explain the fundamental economic approach to organizations is updated to include coverage of the environment and institutions.* Heavier emphasis on institutional and evolutionary perspectives is carried through the text as well as greater coverage of the resource based view of strategy and the introduction of the concept of dynamic capabilities. This is an ideal textbook for a course on Organization and Management from an economic perspective. The text can also be used as a supplement to a larger text on Organization and Management or Strategic Management. Economics students will benefit from a concise introduction to a field that is related, but all too often unexplored. Sytse Douma is professor of Business Administration at Tilburg University. Hein Schreuder is Executive Vice President of Corporate Strategy and Acquisitions at Royal DSM N.V., honorary professor of Business Economics at Maastricht University and Distinguished Visiting Professor at the China Europe International
Keywords: Managerial economics; Unternehmenstheorie; Organisationstheorie; Wirtschaftstheorie; Organisation